Relation between Hypoxic Markers P65, P50, CAIX, and Tumor Stages in Invasive Ductal Carcinoma Subtypes - Eman El-Abd1, Eman; A. Matta, Cecil; Sheta, Manal; El-Kerm, Yasser; Samy Mohammed, Afifi; Benhassine6, Traki; Meftahi, Sarah; Sakr, Shimaa; Elsherbini, Baseem (Université de Bouira, 2015)
Background: Nuclear factor-kappa B (NF-B) family comprises 5 members (p50, p52, relA/p65, c-rel and relB) which are induced in response to a wide variety of stimuli including hypoxia. Continuous activation of NF-B is an important factor in the onset and progression of breast carcinoma. Hypoxia also induces carbonic anhydrase 9 (CAIX) that regulates pH and is linked to poor prognosis in breast cancer. Research motivation: The current study aims to investigate the relation between hypoxic markers, p65, p50, CAIX and tumor stage in IDC (invasive ductal carcinoma) subtypes. Research design/methodology: The study included 31 IDC patients. Breast tissues collected during surgery and classified according to estrogen receptor alpha (ER, progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER-2) status. Normal breast tissues were also collected to serve as self controls. Nuclear protein extracted and both RelA/p65 and p50 protein assessed by ready to use enzyme-linked immunosorbent assay (ELISA) and a transcription factor assay kits; respectively. CAIX protein expression was detected by blotting techniques. Main findings: RelA/p65 concentration significantly increased in breast carcinoma (p = 0.028) irrelevant to tumor stage, size, grade, nodal status, p50, CAIX or IDC subtypes. P50 binding activity significantly increased with higher tumor grade (P = 0.042). A significant inverse correlation was observed between p50 and ER (r = -0.53, p = 0.002) and between CAIX and the number of the involved lymph nodes (r = -0.42, p = 0.020). Implications: Although no relation was observed between p65, p50, and CAIX, binding activity of p50 and CAIX concentration might be used as prognostic markers in IDC.
Keywords: Nuclear factor-kappa B (NF-B); invasive ductal carcinoma (IDC) subtypes; carbonic anhydrase 9 (CAIX)